Challenges Faced by Indian International Students in the US: Challenges of Indian International Students - Chennamsetti, Prashanti (Journal of Interdisciplinary Studies in Education, 2021)
Transiting to an unfamiliar academic culture poses several challenges for students. These challenges are more profound for international students who leave their home country to come to the host country in pursuit of higher studies. The purpose of the present study is to explore such challenges that hindered the adjustment of six Indian international students studying in a US university, using the phenomenological methodology. The data analysis generated five themes related to the challenges encountered: (1) living away from family and friends, (2) difficulty in expressing, (3) multitasking, (4) difficulty in fitting in, and (5) lack of positive attitude. Findings have implications for US universities. Higher educational institutions can play an essential role in addressing the challenges to facilitate a positive academic experience for international students.